NAAL: 뉴로모픽 아키텍처 추상화 기반 이기종 IoT 기기 제어용 소프트웨어 - 조진성(cho jinsung); 김봉재(Bongjae Kim) (Korean Institute of Smart Media, 2022)
Neuromorphic computing generally shows significantly better power, area, and speed performance than neural network computation using CPU and GPU. These characteristics are suitable for resource-constrained IoT environments where energy consumption is important. However, there is a problem in that it is necessary to modify the source code for environment setting and application operation according to heterogeneous IoT devices that support neuromorphic computing. To solve these problems, NAAL was proposed and implemented in this paper. NAAL provides functions necessary for IoT device control and neuromorphic architecture abstraction and inference model operation in various heterogeneous IoT device environments based on common APIs of NAAL. NAAL has the advantage of enabling additional support for new heterogeneous IoT devices and neuromorphic architectures and computing devices in the future. 뉴로모픽 컴퓨팅은 일반적으로 CPU와 GPU를 이용하여 신경망 연산을 하는 것보다 전력, 면적, 속도 측면에서 매우 뛰어난 성능을 보여준다. 이러한 특성은 에너지 사용량이 중요시되는 자원 제약적인 IoT 환경에 매우 적합하다. 하지만 뉴로모픽 컴퓨팅을 지원하는 이기종 IoT 기기에 따라 환경설정 및 응용 프로그램 동작을 위한 소스코드의 수정이 필요하다는 문제점을 가지고 있다. 이러한 문제점을 해결하고자 본 논문에서는 NAAL을 제안하고 구현하였다. NAAL은 공통의 API를 기반으로 다양한 이기종 IoT 기기 환경에서 IoT 기기의 제어와 뉴로모픽 아키텍처의 추상화 및 추론 모델 동작에 필요한 기능을 제공한다. NAAL은 향후 새로운 이기종 IoT 기기 및 뉴로모픽 아키텍처와 컴퓨팅 장치의 추가적인 지원이 가능하다는 장점을 가진다.